Beyond Defining the Smart City. Meeting Top-Down and Bottom-Up Approaches in the Middle - Breuer, Jonas; Walravens, Nils; Ballon, Pieter (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper aims to better frame the discussion and the various, divergent operationalisations and interpretations of the Smart City concept. We start by explicating top-down approaches to the Smart City, followed by what purely bottom-up initiatives can look like. We provide a clear overview of stakeholders’ different viewpoints on the city of tomorrow. Particularly the consequences and potential impacts of these differing interpretations and approaches should be of specific interest to researchers, policy makers, city administrations, private actors and anyone involved and concerned with life in cities. Therefore the goal of this article is not so much answering the question of what the Smart City is, but rather what the concept can mean for different stakeholders as well as the consequences of their interpretation. We do this by assembling an eclectic overview, bringing together definitions, examples and operationalisations from academia, policy and industry as well as identifying major trends and approaches to realizing the Smart City. We add to the debate by proposing a different approach that starts from the collective, collaboration and context when researching Smart City initiatives.